Herzfrequenzvariabilität bei der Anwendung der PMR und suggestiver Entspannung - Nitzsche, N.; Oelze, J.; Ludorff, N.; Schulz, H. (Herzfrequenzvariabilität: Gesundheitsförderung - Trainingssteuerung - Biofeedback. Internationales Symposium am 29. und 30. Oktober., 2011)
Background and Objective: Relaxation techniques are used in rehabilitation and health sports depending on indication and goal. Generally, active and passive methods can be distinguished. The goal is to reduce physiological and psychological stress reactions by means of relaxation and thus affect the vagal tone. The aim of the study was to monitor the influence of one passive and one active relaxation method on measurable parameters of HRV.